ANALYZING THE TYPES OF ALLUSION AND ITS APPLICATION IN NADER NADERPOUR POEM - Hasan Lakziyan, Dr. Shabany, Dr. Parvin Dokht Mashhoor, Dr. Mahboubeh Zia Khodadadian (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Nader Naderpour is one of the prominent contemporary romantic poets who has left many outstanding works. He has used different methods for explaining his intended content to the audience. The allusion is one of his literary tricks. The main purpose of the present research is to investigate the quality of application of this figure of speech in the poems of Naderpour. The present research has been done through the descriptive method and by analyzing content and relying on library resources and research articles. The results of the research show that literary allusion in poems of Naderpour had more frequency. He has mostly focused on the poems of Saadi and Hafiz. These allusions are mainly reflective of the emotional and lyric attitudes of the pots. Moreover, his poems have strings of social and political criticism. The diversity of Iranian, Greek, and Saami myths also have been prominent in myth allusions that indicate a wide study of the poet about the literature and culture of different nations.